+0  
 
0
356
3
avatar

What is f'(x) when f(x) = 10-10e**(-2x)?

Guest Apr 11, 2017
 #1
avatar
0

d/dx (e^(-2x) )      = -2e^(-2x)      from the Chain Rule.                 

So f'(x) =  -20 e^(-2x)

Guest Apr 11, 2017
 #3
avatar+27128 
0

You've forgotten one of the minus signs Guest #1

Alan  Apr 11, 2017
 #2
avatar+27128 
+2

f'(x) = 0 - 10*(-2)e-2x  or  f'(x) = 20e-2x 

.

Alan  Apr 11, 2017

16 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.